Desiree’s Self-Actualization in The Vanishing Half by Brit Bennett - Aprilia Ratna Susanti; Muizzu Nurhadi (English Literature Studi Program Universitas Islam Makassar, 2025)
This study is entitled Desiree’s Self-Actualization in The Vanishing Half by Brit Bennett. This study aims to understand self-actualization and self-actualization traits of Desiree as the central character in the novel, how the character fulfils self-actualization needs, and kinds of self-actualization traits in the novel. It used a descriptive qualitative method as the research design and Maslow’s hierarchy of needs as the theory of this study. The results of this study showed that the protagonist successfully achieved self-actualization indicated trough 15 self-actualization traits i.e., Desiree, the protagonist, shows self-respect, personal courage, truth, greater frustration tolerance, genuineness, honesty, self-acceptance, kindness, unselfishness, bigness, calmness and peace of mind. One of Maslow’s indicators, describes that people who actualized themselves are living their authentic life, less fear and accept their true self. In short, this study highlights that self-actualisation can only be achieved once a person has met all their other needs. Furthermore, the resolution of conflict within the story is a key factor in the protagonist’s attainment of self-actualisation.